Raman spectroscopy in oral cavity and oropharyngeal cancer: a systematic review. Issue 11 (November 2022) - Faur, C.I.; Falamas, A.; Chirila, M.; Roman, R.C.; Rotaru, H.; Moldovan, M.A.; Albu, S.; Baciut, M.; Robu, I.; Hedesiu, M.
Abstract: Due to the high incidence of head and neck cancer and under-diagnosis in the early stages, non-invasive and highly accurate diagnostic tests are required for cancer detection. Recent advances in Raman spectroscopy techniques have yielded promising sensitivity and specificity results in the evaluation of cancer. The aim of this study was to investigate the potential value of Raman spectroscopy in oral cavity and oropharyngeal cancer diagnosis based on currently available scientific papers. A search of the PubMed database was performed using a specific strategy and according to the PRISMA guidelines. Raman spectroscopy achieved a maximum accuracy of 98% in cancer detection, while accuracy was 97.24% for tumour grading evaluation, 95% for cancer treatment assessment, and 77% for the detection of cancer recurrence. Moreover, early-stage cancer can be identified by Raman spectroscopy investigation of liquid biopsy samples. An in vivo technique with direct mucosa examination by fibre-optic Raman spectroscopy obtained a maximum accuracy of 94% in cancer diagnosis. The most prominent markers of the presence of malignancy were an increase in Raman signal intensity for proteins, nucleic acids, and water and a decrease for lipids. These cancer discriminants were detected in both fingerprint and high wavenumber regions. In conclusion, Raman spectroscopy is a promising tool for oral cavity and oropharyngeal cancer screening.